(untitled) (Journal of International Studies, 2020)
The provinces of Patani, Yala and Narathiwat are witnessing waves of violence especially since January 2004. Many see the violence as a sign of the resurgence of separatism. There are many reasons for this. The Malay Muslims in these provinces are not happy with the government attempts to assimilate/integrate them into the mainstream Thai society. There is an inherent fear among them that government policies are meant to erode their Malay Muslim identity in the majority Buddhist nation. They want to retain a separate political, cultural and religious identity as Patani Malay Muslims. This paper discusses how some of the government policies have contributed to the Patani Malay Muslim grievances against the government in Bangkok.